Pengaruh Retun On Equity, Return On Asset, Net Profit Margin, Dan Expense Before Interest And Taxesterhadap Harga Saham Pada Perusahan Transportasi Yang Terdaftar Di Bursa Efek Indonesia - Rivolino Cesio Yunansalasa; Sri Trisnaningsih (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of return on assets, return on equity, net profit margin, and expense before taxes and interest on stock prices. The population used is transportation companies listed on the Indonesian stock exchange in the 2019-2021 period. Determination of the sample in this study using purposive sampling and there are 30 companies that meet the criteria to be sampled. This study uses multiple linear regression analysis which shows that return on assets, return on equity, net profit margin, and earnings before taxes and interest have a significant effect simultaneously. return on assets partially significant effect on stock prices, while return on equity, net profit margin, and expense before taxes and interest have no simultaneous significant effect on stock prices